Offshore energy structures in the North Sea: Past, present and future. (June 2023) - Martins, Maria Clara Iruzun; Carter, Matt ID; Rouse, Sally; Russell, Debbie JF
Abstract: Offshore man-made structures (MMS) such as oil and gas (O&G) platforms, pipelines and wind energy developments are present in shelf seas worldwide and can potentially influence ecosystem dynamics and services. The number, type and age of these structures is changing as the wind energy sector expands whilst O&G structures reach the end of economic viability and are decommissioned. The North Sea is an area which supports major offshore energy production and consequently has a particularly high density of MMS which, according to the OSPAR 98/3 decision, will need to be removed after cessation of operations. To inform effective policy decisions, a comprehensive understanding of the impact of MMS on North Sea ecosystem is required. A major challenge to this is the lack of a comprehensive MMS database with up-to-date and accurate metadata (e.g. structure type, installation date) and locations. We found that existing databases are spatially restricted and/or contain conflicting locational data and, when present, metadata. When used in scientific studies to support policy decisions, such gaps and errors limit inference and could lead to spurious results. Here we develop a comprehensive spatial database of MMS including O&G platforms, pipelines and wind turbines in the North Sea. This allowed examination of temporal trends in how North Sea MMS have changed in number, type and location. The generated database will be useful for a range of stakeholders ranging from ecologists, engineers, policymakers, industry advisors and geoscientists. Indeed, such a database is fundamental for robust research studies required to inform effective and sustainable policy decisions, including review of the OSPAR 98/3 regulation.